2018
DOI: 10.1002/pbc.27304
|View full text |Cite
|
Sign up to set email alerts
|

Insulin and glucose homeostasis in childhood cancer survivors treated with abdominal radiation: A pilot study

Abstract: This study suggests that radiation-induced damage to the insulin-producing β-cells is an unlikely explanation for the early derangements in glucose metabolism observed after abdRT. Research into alternative pathways leading to diabetes after abdRT is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 34 publications
0
9
1
1
Order By: Relevance
“…Also, HL patients required abdominal and cervical irradiation, yet we retrieved only TBI as a risk of hyperglycaemia development in our ALL cohort. Abdominal, cervical and cranial radiation did not appear to induce hyperglycaemia in our study, although this is contrary to findings in other studies which suggested the effect of abdominal radiation 30–32 . Strengths of our study include the large sample size of ALL patients, inclusion of risk factors for hyperglycaemia, complete patient records and numerous harmonized blood glucose data for ALL and NHL.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Also, HL patients required abdominal and cervical irradiation, yet we retrieved only TBI as a risk of hyperglycaemia development in our ALL cohort. Abdominal, cervical and cranial radiation did not appear to induce hyperglycaemia in our study, although this is contrary to findings in other studies which suggested the effect of abdominal radiation 30–32 . Strengths of our study include the large sample size of ALL patients, inclusion of risk factors for hyperglycaemia, complete patient records and numerous harmonized blood glucose data for ALL and NHL.…”
Section: Discussioncontrasting
confidence: 99%
“…Abdominal, cervical and cranial radiation did not appear to induce hyperglycaemia in our study, although this is contrary to findings in other studies which suggested the effect of abdominal radiation. 30 , 31 , 32 Strengths of our study include the large sample size of ALL patients, inclusion of risk factors for hyperglycaemia, complete patient records and numerous harmonized blood glucose data for ALL and NHL. Furthermore, we studied the incidence of hyperglycaemia from the initiation of cancer treatment and not only during remission (after 2 years).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the pathophysiology of diabetes after abdominal radiation, the epidemiologic data would suggest that damage to the insulin-producing b cells concentrated in the tail of the pancreas is the key etiologic factor in development of diabetes in this population. However, the limited clinical data regarding the role of insulinopenia in the development of diabetes after abdominal radiation are inconsistent (22); moreover, more recent data suggest a role for insulin resistance rather than insulinopenia in the pathogenesis of diabetes (26). Further studies to clarify the mechanisms leading to diabetes after abdominal radiation are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Our group recently evaluated pancreatic autoantibody status (glutamic acid decarboxylase [GAD-65], insulin autoantibodies, islet antigen-2) in 40 survivors of childhood cancer exposed to abdominal radiation [58]. While a variety of glucose and insulin derangements were noted in this investigation, none of the participants had more than one positive pancreatic autoantibody, suggesting that autoimmunity is not the underlying etiology of posttherapy diabetes.…”
Section: Diabetesmentioning
confidence: 99%